Maternal tobacco use and risk for congenital anomalies - Hiremath, Prabhuswami; Patange, R. P.; Salunkhe, J. A.; Mohite, Vaishali R.; Pawar, Ajit; Mulani, Afsana (International Journal Of Community Medicine And Public Health, 2019)
Background: Over a period of decades non genetic causes are controlled and mortality and morbidity is considerable reduced due to malformation. Although 50% of causes for malformation are unknown origin, but, with primary prevention 50% of birth defects could be prevented. Research for finding the risk factors are continuous and such results would help to implement preventive strategies to improve maternal and child health. Methods: This is cross sectional; hospital based study, conducted in Krishna Hospital Karad, included all the Pregnant Mother diagnosed to have congenital birth defected foetus through antenatal examinations, delivered baby with diagnoses of congenital malformation, who were admitted at tertiary care hospital Karad. Results: Total 283 cases were diagnosed with birth defects. Parent’s history for tobacco use states that 16 (5.7%) mothers and 149 (53%) of fathers of malformed babies used tobacco. Among these 16 (5%) tobacco user mothers, maximum babies 5 (1.7 %) babies had born with neural tube defect and among fathers 149 (53%) maximum babies 41 (14%) circulatory system defect. Conclusions: There is a need to make the rural women aware about hazardous effects of use of mishri through health education sessions to wean them out of this addiction, which is passed from one generation to the next as a tradition at an early age.